New Method and Tool for TEM Samples Preparation - Boguslavsky, D.; Cherepin, V.; Polubotko, Y.; Smith, C. (Металлофизика и новейшие технологии, 2013)
А new tool for TEM sample preparation, which allows preparing a thin lamella with thickness less than 20 nm surrounded by and embedded in bulk material, is presented. The main advantages of this system are low ion milling induced damage (less than 2 nm in depth), low process time (1—2 hours), in situ sample monitoring during ion milling (topography and sample thickness), and large treated area (5—30 μm along the area of interest). Comparison of few kinds of working substance of ion sources as well as schemes or drawings of key components of the tool are presented. Представлено нову методику і технологію виготовлення зразків для ПЕМ, яка уможливлює підготувати зразок завтовшки до 20 нм, оточений об’ємним матеріалом і втілений у нього. Головна перевага системи полягає в малій товщині шару пошкоджень, спричинених йонним обробленням (менше 2 нм), в малому часі оброблення (1—2 години), в моніторинґу зразка під час йонного фрезерування (топографія і товщина зразка) і у великій площі, що обробляється (5—30 мкм вздовж області, яка являє інтерес). Виконано порівняння декількох типів робочої речовини для йонних джерел, наведено схеми або креслення ключових вузлів пристрою. Представлена новая методика и технология приготовления образцов для ПЭМ, позволяющая подготовить образец толщиной до 20 нм, окружённый объёмным материалом и вмурованный в него. Главным преимуществом системы является малая толщина слоя повреждений, индуцированных ионной обработкой (меньше 2 нм), малое время обработки (1—2 часа), мониторинг образца во время ионного фрезерования (топография и толщина образца) и большая обрабатываемая площадь (5—30 мкм вдоль интересующей области). Проведено сравнение нескольких рабочих веществ для ионных источников, приведены схемы или чертежи ключевых узлов устройства. The authors would like to thank the staff of SELA and PETRC of Ukraine for taking part in the development and fabrication of Xact. In particular, D. Viazovsky and T. Krasovsky for electronics development, V. Kontorov and V. Isyanov for technical documentation development, D. Farhana, L. Berner for software development, A. Berner, A. Bekkerman, A. Eizner, V. Kuchik, S. Yakovlev, G. Aharonov, all who made this achievement real by their hard work and talent.